Diagnóstico microbiológico e parasitológico em alface (lactuca Sativa l.) Comercializada em município do semiárido brasileiro - Batista, João Inácio Lopes (2018)
Lettuce (Lactuca sativa L.) stands out as the most popular hardwood and consumed in Brazil, presenting importance in public health for its nutritional contribution as well as for the possibility of disease transmission, since it is commonly consumed without cooking and can contaminated by parasites and / or pathogenic micro-organisms. Errors in handling and environmental contamination caused, for example, by lack of basic sanitation can contribute to the spread of foodborne diseases, highlighting the social importance of parasitic and microbial research, which can provide data on the hygienic-sanitary conditions involved in the production, storage, transport and handling of food. In this context, the objective of this work was to diagnose the microbial and parasitic quality of lettuce commercialized in the city of Mossoró, State of Rio Grande do Norte. The study was conducted with samples collected by direct purchase in public street market stalls and supermarkets in the city. For the microbiological analysis, the Most Probable Number (MPN) technique was applied for the determination of total coliforms and thermotolerant coliforms, in addition to the presence of Salmonella sp. For the parasitological analysis, we used the Hoffman spontaneous sedimentation method with modifications, and the Faust centrifugal-flotation method. Statistical analysis was performed using the χ2 test and Fisher's exact test, with a significance level of 5%. For the microbiological analyzes, a sample per establishment was analyzed, where 100% (12/12) showed contamination by total coliforms, 25% (3/12) thermotolerant coliforms above the allowed and absence of Salmonella sp. Regarding parasitic contamination, 62.5% (45/72) were contaminated, and the parasites were diagnosed: hookworms 40.3% (29/72), Strongyloides sp. 29.2% (21/72), Ascaris sp. 1.4% (1/72), Entamoeba histolytica / dispar 1.4% (1/72), Endolemax nana 1.4% (1/72) and Entamoeba coli 2.8% (2/72). Another finding of relevance was the physical contamination with the diagnosis of insects in 19.4% (14/72), in addition to Oesophagostomum sp. 16.7% (12/72) and other free-living nematode larvae in public health. However, there was no difference in parasite and microbial quality among the commercialization sites of this study. Thus, it is evidenced the presence of microbial and parasitic contamination, determining the low hygienic-sanitary quality of the studied lettuce and the potential health risk to which the population is exposed